Mengembangkan dan Mengoptimalkan Media Pembelajaran Pendidikan dalam Aspek Teknologi di Desa Rejotangan - Rohmatus Syafi'ah; Nourma Oktaviarini; Nurna Listya P. (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
The results of observations in the village of Rejotangan Tulungagung show that the obstacles experienced by students who are in elementary school in online learning are the limited use of learning technology, which is caused by the absence of guidance from both teachers and parents in the use of learning technology in the digital era. Learning is carried out only through WhatsApp (WA) group media for sharing materials and giving assignments without using other digital learning media. The condition of the lack of knowledge on the use of learning technology in the digital era will certainly be a long-term obstacle if it is not overcome, therefore this program of community service activities in the village of Rejotangan Tulungagung is held to optimize and develop educational learning media, especially for elementary school teachers or equivalent. Results of the interview with Wakakur MIN 5 Tulungagung, Rejotangan village, it is known that the media used in online learning is WA group and google classroom which causes students to be less enthusiastic. This community service activity aims to introduce and assist MIN 5 Tulungagung teachers in making effective learning media using Kinemaster which is later expected to increase student enthusiasm in online learning. The method of implementing the activities is in the form of a problem solving framework and the realization of problem solving. The targets in this activity are 15 teachers from low and high grades. The result of this activity is the achievement of the target of 80% which means the activity is successful and the participants are enthusiastically followed from beginning to end. The obstacle in this activity is that there are 2-3 teachers whose cellphone memory is not sufficient to download the kinemaster application. The follow-up to this activity is that similar activities are carried out with a longer time.